Expression of sterile-α and armadillo motif containing protein (SARM) in rheumatoid arthritis monocytes correlates with TLR2-induced IL-1β and disease activity. (19th February 2021) - Thwaites, Ryan S; Unterberger, Sarah; Chamberlain, Giselle; Gray, Henry; Jordan, Kelsey; Davies, Kevin A; Harrison, Neil A; Sacre, Sandra
Abstract: Objective: Cartilage and bone damage in RA are associated with elevated IL-1β. The effects of IL-1β can be reduced by biological therapies that target IL-1β or TNF-α. However, the mechanisms responsible for increased IL-1β and the effect of anti-TNF-α have not been fully elucidated. Recently, sterile-α and armadillo motif containing protein (SARM) was identified as a negative regulator of toll-like receptor (TLR) induced IL-1β secretion through an interaction with the inflammasome. This study set out to investigate SARM during TLR-induced IL-1β secretion in RA peripheral blood monocytes and in patients commencing anti-TNF-α treatment. Methods: Monocytes were isolated from RA patients and healthy controls; disease activity was measured by DAS28. IL-1β secretion was measured by ELISA following TLR1/2, TLR4 and TLR7/8 stimulation. The mRNA expression of SARM1, IL-1β and the components of the NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome were measured by quantitative PCR. SARM protein expression was measured by western blotting. Results: TLR1/2 activation induced elevated IL-1β in RA monocytes compared with healthy controls ( P = 0.0009), which negatively correlated with SARM1 expression ( P = 0.0086). Lower SARM expression also correlated with higher disease activity ( P = 0.0246). Additionally, patients responding to anti-TNF-α treatment demonstrated a rapid upregulation of SARM, which was not observed in non-responders. Conclusion: Together, these data highlight a potential contribution from SARM to RA pathophysiology where decreased SARM may lead to elevated IL-1β associated with RA pathogenesis. Furthermore, the data additionally present a potential mechanism by which TNF-α blockade can modify IL-1β secretion.